Programa de psicoprofilaxis obstétrica y su Influencia en el comportamiento de las gestantes, Atendidas en el Hospital II ESSALUD – Tarapoto. Junio – Setiembre 2014 - Gaviria Ríos, Katty Giannina (2014)
The present study entitled "Programme of obstetrical psycho and its influence on the Behavior of pregnant women, treated at the Hospital essalud II - Tarapoto. June -September 2014 “; quantitative, analytical, prospective , cross-sectional design "ex Post facto" study whose objective was to determine the influence of the program of Obstetrical psycho behavior of pregnant women, worked with a sample of 30 Pregnant for both the experimental group and the group control, instrument pickup And questionnaire data was Watchlist according ESPERI test , validated by experts , Data is organized based Excel 2010 and SPSS software. V.17 . The results found that: pregnant women who received the program , 50% (15) have Upper and middle of knowledge about the topics covered level , 70 % (21) have Adequate standard of behavior against pregnancy . According dimensions, 100 % (30) have adequate standard of behavior for the protection and care of the female Reproductive system dimension; 96.7 % (29) have an appropriate behavior on Prenatal care and care of pregnant women; 66.7 % (20) are suitable level behavior Gaps in simulated uterine contractions dimension; 73.3 % (22) have appropriate Behavior in simulated breathing and pushing dimension , showing positive influence Of the program. In the control group found that: 50 % (15) have a medium and low Level of knowledge on the subjects, 50% (15) have an adequate level lacking against Pregnancy; 83.3 % (25) came in not providing the protection and care of the female Reproductive system dimension; 53.3 % (16 ) Suitable started lacking in relation to Prenatal care and care of pregnant women ; dimension in simulated uterine Contractions and pushing simulated breathing and 100.0% started not provided. In conclusion Psicoprofilaxis Program Obstetric significantly potentiates the behavior And knowledge of pregnant women.